On Commandment as Refuge: Exploring the Politics of Health and Indigenous African Religion on Covid-19 (The Strategic Review for Southern Africa, 2021)
This paper explores the significance of the turn to the religion of the family and the clan (i.e., indigenous African religion) taking place under the contemporary conditions of Covid-19 in many African countries. It does this in order to exhibit the Africanity that is hidden by this otherwise pragmatic turn. The paper explores this Africanity by drawing from the classical African story of Seila-Tsatsi, which it argues has its roots in religious education. The key aim of its examination of this Africanity is interrogate a politics of health it claims the World Health Organisation advances. The paper does not explore this turn by accounting for the meanings individuals attribute to it but is rather abstract and conceptual in its approach. The argument it makes is that the contemporary turn to the religion of the family and the clan exhibits desire for an inclusive form of relationality that ought to inform fair, equitable and just health outcomes. It argues that the WHO’s politics of health is blind to this model because it stubbornly upholds binary thought.
Keywords: Commandment; Relationality; Remembering; Politics; Covid-19